Psychopathology An International and Interdisciplinary Perspective - Woolfolk, Robert; Allen, Lesley; Durbano, Federico; Irtelli, Floriana (IntechOpen, 2020)
This collection brings together an international array of cutting-edge thinkers who address the basic questions of psychiatry using diverse methods from a variety of different perspectives. The reader is taken to the frontiers of psychiatry and clinical psychology to view the future of the field. With mental health seemingly deteriorating around the world, the need for fresh perspectives is urgent. The authors featured in this volume fulfill that need admirably.